Effect of Ca substitution on the microwave properties and the inhibition of Ag diffusion in Ba1-xCaxMoO4 ceramics. Issue 10 (July 2020) - Zhu, Haikui; Dong, Ye; Gu, Huidong; Bian, Wenjie; Zhang, Qitu
Abstract: Ba1-x Cax MoO4 (0 ≤ x ≤ 0.20) ceramics were prepared from powders to form solid solutions by a solid-state reaction sintering process. The influence of the Ca 2+ content on the microstructure, sintering, densification, microwave dielectric properties and chemical stability of BaMoO4 -based ceramics with Ag metal was discussed in detail. The sintering temperatures of the Ba1- x Ca x MoO4 ceramics were effectively reduced to less than 950 °C by the formation of the solid solutions. Structural analysis indicates that the Ba1-x Cax MoO4 ceramics belong to the class of tetragonal scheelites. The crystal grain size begins to decrease and become more regular as x increases from 0 to 0.12. However, as x continues to increase, a liquid phase begins to appear, and the grain boundaries are no longer clear. The ε r value increases from approximately 8.6 to 9.8 as x increases from 0 to 0.2. The Ba0.92 Ca0.08 MoO4 sample possesses the best microwave dielectric performance, namely an ε r  = 9.3 and the maximum Q × f value of 33593 GHz. The addition of 15 wt% TiO2 or 10 wt% CaTiO3 can effectively change the τ f values of the Ba1-x Cax MoO4 ceramics to approximately 0. The Ba1-x Cax MoO4 ceramic samples can coexist with silver during the LTCC cofiring process.